MARKETING COMMUNICATION TO ENHANCE BRAND IMAGE AT HOTEL FAIRFIELD BY MARRIOTT BALI LEGIAN - Dewi, Komang Tri Herlina; Sagitarini, Luh Linna; Armoni, Ni Luh Eka (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
This istudy aimed to explore how marketing communications are implemented at the Fairfield by Marriott Bali Legian Hotel and to analyze how these efforts influence the hotel's brand image. The research used a quantitative method through simple linear regression analysis, supported by a qualitative approach involving structured interviews. The findings show that the hotel has implemented its marketing communications strategy very effectively. In particular, the use of Instagram has generated strong engagement from followers on the official account, @fairfieldbalilegian. This is further supported by an increase in the account’s performance metrics, as measured using the website phlanx.com. Data analysis reveals that marketing communication plays i a significant i role i in enhancing i the hotel’s brand image. The simple regression analysis produced a constant value of 13.420 and a regression coefficient of 0.777, indicating that for every one-unit increase in marketing communication efforts, the brand image improves by 0.777 units. Furthermore, the coefficient of determination (R²) was found to be 0.794. This means that 79.4% of the hotel’s brand image is influenced by marketing communication activities, while the remaining i 20.6% is affected by other i factors